Experiences of personnel providing shariah-guided support in clinical practice: a qualitative study - Wan Mamat, Wan Hasliza; Mohd Yusri, Intan Nabila; Azmi, Nor Azura; Arini, Merita; Muhammad Kadir, Fairuz Izzaty (IIUM Press, 2025)
Background: Spiritual care is a vital component of holistic healthcare, supporting patients in aligning with their beliefs to foster inner peace and overall well-being. However, there is limited research on the experiences of hospital staff in providing spiritual care. This study aims to explore the experiences of Shariah-compliant hospital staff in delivering spiritual care to hospitalised patients.